Symbolism of the number nine in Tuvan linguoculture (as compared to some Turkic and Mongolian languages) - Bredis, Mikhail A. (The New Research of Tuva, 2023)
The article analyzes Tuvan phraseological units and folklore texts comprising the numerical component “nine”. They were selected by continuous sampling from various lexicographic sources. The author examines them in contrast to the Khakass, Altai, Mongolian, Kalmyk and Buryat languages. Methods of the linguoculturological, descriptive and analytical analysis were used, as well as the method of structural and semantic modeling for analyzing paremiological units. It has been found out that folklore texts, phraseological and paremiological units of Tuvan linguoculture are mostly based on the semantics of the number nine and its sacred character. Numerical symbolism pervades folklore texts, mythology, folk beliefs and rituals. A special similarity in the symbolism of the number nine can be found in the linguocultures of the Mongolian peoples. This is due to the kinship of the Turkic and Mongolian languages within the Altai macrofamily of languages, some features of the common history and the linguistic and cultural transfer of the Tuvans, Mongols and Buryats. It is noted that the symbolism of the number nine in Tuvan and Mongolian linguocultures is largely similar to Chinese symbols. This creates a commonality between the Far East and part of Central Asia.